Web-based instruction for adult learners : an asynchronous delivery model for formal lifelong learning - Nantha Kumar Subramaniam (2013)
Web-based Instruction (WBI) is becoming a favored teaching and learning option in higher education. Unfortunately, the effects of WBI on success, perception and gender have not been clearly demonstrated or sufficiently addressed, especially for adult learners who are engaged in the formal lifelong learning via the popular asynchronous WBI (A-WBI). This paper attempts to address the following objectives: (i) to propose a framework for A-WBI to deliver lessons to adult learners who are enrolled in formal lifelong learning; (ii) to implement the proposed framework; (iii) to explore adult learner perceptions of A-WBI and of how gender influences their perception; (iv) to explore the influence of A-WBI on the adult learner summative assessment (final examination component); and (v) o analyze the relationship between adult learner interaction with A-WBI and their final examination marks. Objectives (i) and (ii) are achieved by using the design and implementation approach while objectives (iii), (iv) and (v) are achieved by an interpretive case study methodology approach. The findings indicate: (i) moderate learner responses for the use of A-WBI when studying have led to poor performance in the summative assessment among adult learners; (ii) female learners are the high-risk group in A-WBI; and (iii) quality interaction in the A-WBI discussion forum has a strong relationship with learner final examination scores. The paper concludes with discussions on the findings and recommendations. (Abstract by author)